Deveplopment and validation of insulin adherence questionnaire (IAQDM) and determination of factors associated with non-adherence among patients with type 2 diabetes mellitus - Singh @ Nui, Shareen A/P Purran (2016)
Introduction: Prevalence of type 2 diabetes mellitus (T2DM) is increasing worldwide and locally. Although various treatments were prescribed to control blood glucose level, the glycaemic target is still not achieved. At present, insulin therapy becomes the mainstay of treatment because of its effectiveness to control blood glucose. However, insulin injection is complex and can contribute to non-adherence problem among insulin treated patients with diabetes. Objective: To develop and validate a new questionnaire to measure adherence with insulin therapy in patients with T2DM. This study also aimed to determine rate of non-adherence, glycaemic control and factors associated with insulin therapy. Methodology: This study used qualitative design in the initial part of the study to choose appropriate themes for the IAQDM and quantitative design was utilised for the rest of the study. Interviews were conducted among 30 patients with T2DM on insulin therapy using developed and validated semi-structured interview guide. Items for the new IAQDM were selected from patients’ interviews, literature reviews, and consultation with the experts. The IAQDM was validated among 156 patients with T2DM on insulin therapy at the Diabetic Centre, Hospital Universiti Sains Malaysia,Kubang Kerian, Kelantan, Malaysia. Rate of insulin non-adherence, glycaemic control and factors associated with insulin non-adherence were measured in 355 patients with type 2 diabetes mellitus. Transcript data from the initial interviews were analysed for relevant themes using NVivo software version 10.0. Data for sociodemography, insulin non-adherence rate, glecemic control and factors associated with insulin therapy were analysed quantitatively using Statistical Package of Social Science (SPSS) version 22. Result: The IAQDM consisted of 35 items and four domains: domain 1 (barriers with insulin injection), domain 2 (self-monitoring of insulin and blood glucose), domain 3 (adherence with insulin injection) and domain 4 (dietary adjustment with insulin therapy). Overall Cronbach’s alpha value for all the 35 items in the IAQDM was 0.82. Cronbach’s alpha values for each domain are 0.82, 0.88, 0.85 and 0.82 respectively. Non-adherence rate with insulin therapy among patients with type 2 diabetes was 81%. Majority (98%) of patients on insulin therapy did not achieve the target HbA1c of < 6.5%. Duration of insulin therapy, frequency of insulin injections and fasting plasma glucose were identified as independent and significant factors to non-adherence with insulin therapy. Conclusion: A new IAQDM with very good psychometric properties to measure adherence with insulin therapy has been developed. Adherence with insulin therapy and glycemic control among patients with T2DM were very poor. Identification of several factors contributed to insulin non-adherence can provide a very useful guide for screening, managing, monitoring, and improving adherence with insulin therapy.